ARCHITECTURE, TYPES, AND ISSUES OF WIRELESS SENSOR NETWORKS - Mirjalolova , Nargiza (UZBEKISTAN — 2030: PROSPECTS FOR INNOVATION, SCIENCE AND EDUCATION, 2025)
The article discusses the structure, operating principles, and practical applications of wireless sensor networks (WSN) technology. The WSN system consists of numerous independent sensor nodes that enable the monitoring of physical processes in the environment, as well as data collection and analysis. The work provides detailed information about the WSN architecture and its main components: sensor module, radio module, microcontroller, power supply, and base station. It also analyzes network topologies and types (terrestrial, underground, underwater, multimedia, and mobile sensor networks). Advantages such as energy efficiency, flexibility, and real-time monitoring are noted, while disadvantages include security vulnerabilities, limited communication range, and complexities in deployment. This research aims to highlight the possibilities for improving the efficiency of WSN systems and their application in various practical fields.